Nutrient timing for peak performance - Skolnik, Heidi; Chernus, Andrea (Champaign, IL, 2010)
With guidelines specific to training and competition, as well as sample meal and snack plans, you'll see how certain nutrients in precise amounts at specific times can improve consistency of energy, speed recovery, increase the building effects of strength training, diminish muscle breakdown, improve immune function, and minimize your risk of injury
Keywords: Athletes- Nutrition; Chernus; Sportifs Alimentation